The North Wyke Farm Platform: effect of temperate grassland farming systems on soil moisture contents, runoff and associated water quality dynamics. (29th June 2016) - Orr, R. J.; Murray, P. J.; Eyles, C. J.; Blackwell, M. S. A.; Cardenas, L. M.; Collins, A. L.; Dungait, J. A. J.; Goulding, K. W. T.; Griffith, B. A.; Gurr, S. J.; Harris, P.; Hawkins, J. M. B.; et al.
Summary: The North Wyke Farm Platform was established as a United Kingdom national capability for collaborative research, training and knowledge exchange in agro‐environmental sciences. Its remit is to research agricultural productivity and ecosystem responses to different management practices for beef and sheep production in lowland grasslands. A system based on permanent pasture was implemented on three 21‐ha farmlets to obtain baseline data on hydrology, nutrient cycling and productivity for 2 years. Since then two farmlets have been modified by either (i) planned reseeding with grasses that have been bred for enhanced sugar content or deep‐rooting traits or (ii) sowing grass and legume mixtures to reduce nitrogen fertilizer inputs. The quantities of nutrients that enter, cycle within and leave the farmlets were evaluated with data recorded from sensor technologies coupled with more traditional field study methods. We demonstrate the potential of the farm platform approach with a case study in which we investigate the effects of the weather, field topography and farm management activity on surface runoff and associated pollutant or nutrient loss from soil. We have the opportunity to do a full nutrient cycling analysis, taking account of nutrient transformations in soil, and flows to water and losses to air. The NWFP monitoring system is unique in both scale and scope for a managed land‐based capability that brings together several technologies that allow the effect of temperate grassland farming systems on soil moisture levels, runoff and associated water quality dynamics to be studied in detail. Highlights: Can meat production systems be developed that are productive yet minimize losses to the environment? The data are from an intensively instrumented capability, which is globally unique and topical. We use sensing technologies and surveys to show the effect of pasture renewal on nutrient losses. Platforms provide evidence of the effect of meteorology, topography and farm activity on nutrient loss.